¿Qué saben los hombres del valle de Aburrá acerca de la salud reproductiva? (2012)
ABSTRACT: To evaluate the information and perceptions about reproductive health of a group of men in the Aburra Valley, Antioquia, Colombia. Methods: 478 men aged between 10 and 58 years were surveyed by means of a form including 34 general questions on reproductive health. Results: 58.6% of the surveyed men had initiated intercourse between the ages of 13 and 18 years; 97.9% had some knowledge on sexually transmitted diseases; 76% had not turned to a professional advisor before choosing a contraceptive method; 16.1% did not know which the function of an urologist is; 5% believed that varicocele only occurs in older men, and 22% did not know what a sperm analysis is. Conclusion: Results of this survey allow us to have a more accurate understanding of the behavior and knowledge of a group of men in Antioquia, Colombia about reproductive health. Additionally, they highlight the need to take action involving men in basic aspects such as family planning, the desired number of children and protection against sexually transmitted infections.